Abilities to Express Lexical Units in Translation - NabiyaIdrisovna, Abdullayeva; Mavjuda Maqsudovna, Artikova; Dilora Abduraxmonova, Sulaymonova; Zarina Raxmatovna, Fattoyeva (International Journal of Psychosocial Rehabilitation, 2020)
A person who is expressing his thoughts through language does not use new words in thinking, but uses words in his vocabulary. The translator also uses words in the dictionary of the language when translating their thoughts. Therefore, the vocabulary in the mind of the translator becomes enriched depending on the language capabilities of the translator. Languages, however, differ in their expressive capabilities, including their breadth and narrowness.